Intraocular lens power estimation for future emmetropia in pediatric cataract surgery - Lottelli,Antonio Carlos (2022)
ABSTRACT Purpose: Creating models, in pediatric cataracts, to estimate kerotometry and axial length values at future ages, based on kerotometry and axial length measured at surgery, to estimate the intraocular lens power for emmetropia in future ages. Methods: Eyes with bilateral cataract and kerotometry and axial length measured at surgery and at least one postoperative examination with kerotometry and axial length measurements, were considered for this study. The models to estimate future kerotometry and axial length values were created considering (1) kerotometry and axial length measured at surgery, (2) the average slope of kerotometry and axial length logarithmic regression created for every single eye and (3) age at surgery. The intraocular lens for future ages can be estimated using these values in third generation formulas. The estimation errors for kerotometry, axial length and intraocular lens were also calculated. Results: A total of 57 eyes from 29 patients met the inclusion criteria. The average age at the surgery and follow-up was 36.96 ± 32.04 months and 2.39 ± 1.46 years, respectively. The average slope of logarithmic regression created for every single eye were -3.286 for kerotometry and +3.189 for axial length. The average absolute estimation errors for kerotometry and axial length were respectively: 0.61 ± 0.54 D and 0.49 ± 0.55 mm, and for intraocular lens using SRK-T, Hoffer-Q and Holladay I formulas were: 2 . 04 ± 1 . 73 D , 2 . 49 ± 2 . 10 D and 2 . 26 ± 1 . 87 D, respectively. Conclusions: The presented models could be used to estimate the intraocular lens power for emmetropia at future ages to guide the choice of the intraocular lens power to be implanted in pediatric cataract.